Preparation of polymethacrylate monolith modified with cysteine for the determination of Cr(iii) ions. Issue 44 (10th July 2018) - Liu, Dan; Pan, Junli; Tang, Jianghong; Lian, Ning
Abstract : In this study, a simple and rapid polymer monolith microextraction procedure was developed for the determination of Cr(iii ) ions by inductively coupled plasma-atomic emission spectrometry. Abstract : In this study, a simple and rapid polymer monolith microextraction procedure was developed for the determination of Cr(iii ) ions by inductively coupled plasma-atomic emission spectrometry. A monolithic column modified with cysteine was synthesized and characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, thermal gravimetric analysis, specific surface area analysis and pore size distribution analysis. The influences of analytical parameters such as sample pH, adsorption time, eluent type, and coexisting ions were examined. The limit of detection (LOD) and limit of quantification (LOQ) for Cr(iii ) ions were 0.005 μg mL −1 and 0.017 μg mL −1, and the relative standard deviation (RSD) was 7.4% ( n = 5). The prepared cysteine functionalized monolithic column displayed good enrichment capacity and was successfully applied to the determination of Cr(iii ) ions in real samples.